Smart Packaging Based on Pectin and Anthocyanin from Purple Sweet Potato Extract (Ipomoea batatas L) with the Addition of Lemongrass (Cymbopogon citratus) Essential Oil - Kistriyani, Lilis; Puspasari, Ifa; Pratiwi, Yulistia; Putri, Syifa Catur Srihadi; Rahayu, Hikmah Muji; Qothrunnada, Syifa Ayu Alsadilla (Faculty of Agricultural Technology, Universitas Semarang, 2025)
Purple sweet potato (Ipomoea batatas L) is one of the tubers that contain anthocyanin compounds because it has natural dyes. Anthocyanins derived from purple sweet potatoes have properties sensitive to changes in pH, so purple sweet potatoes are the right choice to be used as an alternative to natural dyes. Changes in pH that occur in food spoilage are the reason for making and developing smart packaging films based on pectin and anthocyanins derived from purple sweet potato extract by adding lemongrass essential oil. This research aims to determine the effect of purple sweet potato extract anthocyanin levels and kitchen lemongrass essential oil levels on the physical and pH-sensitive properties of the resulting film and determine the performance of the film produced from pectin with the addition of purple sweet potato extract anthocyanins and kitchen lemongrass essential oil as packaging. smart to monitor the freshness of chicken fillet meat. There are three methods used in this research, namely purple sweet potato extraction, film making from pectin-anthocyanin-essential, and film application from pectin-anthocyanin-essential. The research phase was purple sweet potato extract with a concentration of 0%, 10%, 20%, and essential oil 0 mL, 0.5 mL. It added 1 mL of these to the pectin film solution. We are observing color changes, mechanical properties, pH-sensitive properties of films, and film biodegradability. Then, perform measurements of light transmittance and opacity, film thickness, water content, and water vapor permeability. After that, apply a film to detect the freshness level of chicken fillet meat. This research concludes that the anthocyanin content of purple sweet potato extract and essential oil of lemongrass has a significant effect on the physical properties of the pectin-anthocyanin-essential film